2018
DOI: 10.1038/s41467-018-04256-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversification by enhanced genome restructuring after induction of multiple DNA double-strand breaks

Abstract: DNA double-strand break (DSB)-mediated genome rearrangements are assumed to provide diverse raw genetic materials enabling accelerated adaptive evolution; however, it remains unclear about the consequences of massive simultaneous DSB formation in cells and their resulting phenotypic impact. Here, we establish an artificial genome-restructuring technology by conditionally introducing multiple genomic DSBs in vivo using a temperature-dependent endonuclease TaqI. Application in yeast and Arabidopsis thaliana gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 61 publications
(58 reference statements)
3
51
0
Order By: Relevance
“…Our results also suggest that breaks in repeat molecules are repaired either by NHEJ or HR, where other repeat sequences present in the genome may aid in the repair process. Similar observations have also been made previously in Saccharomyces cerevisiae , where DSBs were generated with gamma radiation, HO-endonuclease, or CRISPR 5456 . In all of these studies, multiple copies of Ty elements were found to be involved in the generation of translocations.…”
Section: Discussionsupporting
confidence: 87%
“…Our results also suggest that breaks in repeat molecules are repaired either by NHEJ or HR, where other repeat sequences present in the genome may aid in the repair process. Similar observations have also been made previously in Saccharomyces cerevisiae , where DSBs were generated with gamma radiation, HO-endonuclease, or CRISPR 5456 . In all of these studies, multiple copies of Ty elements were found to be involved in the generation of translocations.…”
Section: Discussionsupporting
confidence: 87%
“…rKDmacro measures changes in chromosome and fundamental numbers at the genomic level, whereas rKDmicro measures subchromosomal rearrangements (SCR) that do not significantly affect the overall cytogenetic organization of the genome. We suggest that these different cytogenetic levels of structural change reflect two different modes of genome dynamics and instability: rKDmacro reflects double strand breaks in DNA (DSB) and Robertsonian translocations (Rb) that likely occur during meiosis (Pardo-Manuel de Villena and Sapienza 2001, Graphodatsky, Trifonov et al 2011, Romanenko, Perelman et al 2012, while rKDmicro reflects DSBs that occur for the most part during interphase of the germline cell cycle , Shrivastav, De Haro et al 2008, Shibata, Conrad et al 2011, Ambrosio, Di Palo et al 2016, Muramoto, Oda et al 2018). This hypothesis, however, remains to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently established a TAQing system to induce DSBs into the nuclear genome (Muramoto et al , ). In this system, the TaqI restriction endonuclease, which recognizes and cleaves the four‐base palindromic DNA sequence TCGA, was selected as an agent for introducing DSB‐induced genome instability, because TaqI exhibits optimal activity at 65°C and a lower level of activity at temperatures ≤37°C (Zebala et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Genome rearrangement events are generally caused by double‐stranded breaks (DSBs) and their subsequent mis‐repair. Recently, we have developed the TAQing system (Muramoto et al , ), which efficiently induces extensive DSB damage to the nuclear genome by utilizing restriction endonucleases. Here, to examine whether ptDNAs in higher plants have the potential to restructure and remodel their own organization, we applied this system to ptDNAs by developing plastid‐targeted forms of restriction endonucleases (pREs), and analyzed their effects on the molecular integrity of ptDNA and plant phenotype.…”
Section: Introductionmentioning
confidence: 99%